Us and Them - Abascal, Maria (American Sociological Review, 2015)
How will Hispanic population growth affect black-white relations in the United States? Research on intergroup relations operates within a two-group paradigm, furnishing few insights into multi-group contexts. This study is based on an original experiment that combines behavioral game and survey methods to evaluate the impact of perceived Hispanic growth on attitudes and behavior. Results reveal opposite reactions among blacks and whites. Whites in the baseline condition contribute comparable amounts to black and white recipients in a dictator game, whereas whites who first read about Hispanic growth contribute more to white recipients than to black ones. By contrast, blacks in the baseline condition contribute more to black recipients than to white ones, whereas blacks who first read about Hispanic growth contribute comparable amounts to black and white recipients. Patterns of identification mirror patterns of contributions: whites exposed to Hispanic growth identify relatively more strongly with their racial group than with their national group, whereas blacks exposed to Hispanic growth identify relatively more strongly with their national group than with their racial group. Together, these results suggest that people respond to the growth of a third group by prioritizing the most privileged identity to which they can plausibly lay claim and which also excludes the growing group.